Removal of arsenite [As(III)] and arsenate [As(V)] ions from wastewater using TFA and TAFA resins: computational intelligence based reaction modeling and optimization - Patil-Shinde, V.; Mulani, K. B.; Donde, K.; Chavan, N. N.; Ponrathnam, S.; Tambe, S. S. (Journal of environmental chemical engineering, 2016)
Being significantly toxic, removal of arsenic forms an important part of the drinking- and waste-water treatment. Tannin is a polyphenol-rich substrate that efficiently and adsorptively binds to the multivalent metal ions. In this study, tannin-formaldehyde (TFA) and tannin-aniline-formaldehyde (TAFA) resins were synthesized and employed successfully for an adsorptive removal of arsenite [As(III)] and arsenate [As(V)] ions from the contaminated water. Next, a computational intelligence (CI) based hybrid strategy was used to model and optimize the resin-based adsorption of As(III) and As(V) ions for securing optimal reaction conditions. This strategy first uses an exclusively reaction data driven modeling strategy, namely, genetic programming (GP) to predict the extent (%) of As(III)/As(V) adsorbed on TFA and TAFA resins. Next, the input space of the GP-based models consisting of the reaction condition variables/parameters was optimized using genetic algorithm (GA) method; the objective of this optimization was to maximize the adsorption of As(III) and As(V) ions on the two resins. Finally, the sets of optimal reaction conditions provided by GP-GA hybrid method were verified experimentally the results of which indicate that the optimized conditions have lead to 0.3% and 1.3% increase in the adsorption of As(III) and As(V) ions on TFA resin. More significantly, the optimized conditions have increased the adsorption of As(III) and As(V) on TAFA resin by 3.02% and 12.77%, respectively. The GP-GA based strategy introduced here can be gainfully utilized for modeling and optimization of similar type of contaminant-removal processes.

Adsorptive removal of strontium(II) using macroporous poly(AGE-co-EGDMA) beads modified with resorcin[4]arene - Mulani, K.; Patil, V.; Chavan, N.; Donde, K. (Bulletin of Materials Science, 2019)
Adsorption behaviour of strontium(II) on macroporous poly(allyl glycidyl methacrylate-co-ethylene glycol dimethacrylate) [poly(AGE-co-EGDMA)] beads modified with resorcin[4]arene was studied using macroporous cross-linked [poly(AGE-co-EGDMA)] beads. The macroporous crosslinked [poly(AGE-co-EGDMA)] beads were synthesized by suspension polymerization techniques, followed by functionalization with amino derivatives of resorcin[4]arene. The poly(AGE-co-EGDMA) beads were characterized by FTIR, 1H and 13C-NMR, elemental analysis and particle-size analysis. The surface morphology of beads was studied by scanning electron microscopy. The functionalized poly(AGE-co-EGDMA) beads were used as adsorbents for strontium removal. The crucial factors including the effect of pH, time, initial concentration of metal ions and adsorbent dose were investigated to optimize the maximum adsorption efficiency of Sr(II). The equilibrium data of strontium(II) ions adsorbed on functionalized poly(AGE-co-EGDMA) beads were analysed by pseudo-first- and pseudo-second-order kinetic models. The pseudo-second-order kinetic model indicated that strontium was adsorbed by chemisorption.
Keywords: Adsorption; AGE-EGDMA beads; resorcin[4]arene; Sr(II)